The scandal of the evangelical mind : with a new preface and afterword - Noll, Mark A., 1946- (Grand Rapids William B. Eerdmans Publising Companry, 2022)
"An award-winning critique of the failure of America's white evangelicals to nurture a thriving intellectual life, with a new preface and afterword by the author"--
"Winner of the Christianity Today Book of the Year Award "The scandal of the evangelical mind is that there is not much of an evangelical mind." So begins this award-winning intellectual history and critique of the evangelical movement by one of evangelicalism's most respected historians. Unsparing in his indictment, Mark Noll asks why the largest single group of religious Americans-who enjoy increasing wealth, status, and political influence-have contributed so little to rigorous intellectual scholarship. While nourishing believers in the simple truths of the gospel, why have so many evangelicals failed to sustain a serious intellectual life and abandoned the universities, the arts, and other realms of "high" culture? Over twenty-five years since its original publication, The Scandal of the Evangelical Mind has turned out to be prescient and perennially relevant. In a new preface, Noll lays out his ongoing personal frustrations with this situation, and in a new afterword he assesses the state of the scandal-showing how white evangelicals' embrace of Trumpism, their deepening distrust of science, and their frequent forays into conspiratorial thinking have coexisted with surprisingly robust scholarship from many with strong evangelical connections"--
Includes bibliographical references and indexes.
Keywords: Evangelicalism -- United States; Learning and scholarship -- Religious aspects -- Christianity